Truques sensoriais em diferentes tipos de distonia e no espasmo hemifacial - Debora Portella Loyola (2010)
Introduction: The dystonia is a syndrome of sustained involuntary muscle contractions always producing twisting and repetitive movements or abnormal postures. Of all movement disorders associated with basal ganglia dysfunction, dystonia is the least understood in terms of underlying pathophysiology. Recent works revealed that basalganglia cortico-striatal-thalamo-cortical motor circuits have an important role in nonmotor cognitive functions, particularly in sensory temporal-spatial discrimination and multisensory integration. The spatial discrimination threshold was found to be abnormal on both hands of patients with unilateral hand dystonia and also on dominant hands ofpatients with cervical dystonia and blepharospasm. The distinctive phenomenon occurring in dystonia is the sensory trick (geste antagonistique). The sensory tricks are tactile stimulation or stimuli from another sensory nature involving the body part affected or not that produce a substantial reduction in dystonia. The hemifacial spasm is aneurological disease with phenomenological characteristics similar to dystonia, but hemifacial spasm is a peripherally myoclonus characterized by involuntary and unilateral, tonic and clonic contractions involving the muscles inerved by ipsilateral facial nerve. Aim: Check the frequency and clinical characterization of sensory tricks in diferents types of dystonia and hemifacial spasm, as well determine changes in spatialdiscrimination during the realization of Grating Orientaion Task and correlate it with sensory tricks. Methods: The volunteers were recruited from Movement Disorder Clinical Ambulatório Bias Fortes UFMG. Participants from both sexs with the diagnosis of dystonia (except the heredo-degenerative) type: blepharospasm (20), cervicaldystonia (21) and writers cramp (10) or hemifacial spasm (26). The volunteers were assessed for a masters student that applied a questionnaire and Mini-Mental State Examination, as well assessed the spatial discrimination by the Grating Orientation Task. Results: The sensory trick presence was bigger in cervical dystonia (81%) whencompared to hemifacial spasm (38,5%) p= 0,004 and to writers cramp (20%), p= 0,001. The spatial discrimination threshold of volunteers dominant hand that do sensory tricks was significantly larger than volunteers that do not sensory tricks (p= 0,019; p <0,050).Conclusions: More than 1/3 from the patients with hemifacial spasm had sensory tricks. Sensory tricks are more common in cervical dystonia (81%) than hemifacial spasm (38,5%) and than writers cramp (20%). Sensory tricks are more common in patients with spatial sensibility deficits.